Respostas

2013-08-18T10:42:29-03:00
x²+3x+2=0
a=1  b=3  c=2
 
Δ  = b² - 4ac 
9 - 4. 1 . 2 ->
Δ  = 1
X = (-b ± raiz de Δ) / 2a
X = (-3 ± raiz de 1) / 2
X = (-3 ± 1) /2
x'= -2
x"= -1


x²-4x-12=0
a=1  b=-4  c=-12 
Δ  = b² - 4ac 
Δ  = (-4)² - 4. 1 . (-12) 
Δ  = 16 + 48
->
Δ  = 64
X = (-b ± raiz de Δ) / 2a
X = (4 ± raiz de 64) / 2
X = (4 ± 8) / 2
X’= 6
X”= -2


x²+12x+20=0
a=1  b=12  c=20
Δ  = b² - 4ac 
Δ  = 12² - 4. 1. 20 
Δ  = 144 - 80
->
Δ  = 64
X = (-b ± raiz de Δ) / 2a
X = (-12 ± raiz de 64) / 2
X = (-12 ± 8) / 2
X’= -10
X”= -2  


x²+17x+60=0

a=1  b=17  c=60
Δ  = b² - 4ac 
Δ  = 17² - 4. 1. 60 
Δ  = 289 - 240
->
Δ  = 49 
X = (-b ± raiz de Δ) / 2a
X = (-17 ± raiz de 49) / 2
X = (-17 ± 7) / 2
X’= -5
X”= -12

Espeero que eu tenha ajudado, quero estrelinhas por favor ok :))
1 5 1